2013
DOI: 10.1007/s40258-013-0030-4
|View full text |Cite
|
Sign up to set email alerts
|

Implications of a Data-Driven Approach to Treatment with Growth Hormone in Children with Growth Hormone Deficiency and Turner Syndrome

Abstract: BackgroundResponse to growth hormone (GH) therapy may vary between individual patients. Therefore the use of GH in children should be closely monitored to avoid over, under, or ineffective treatment regimens. The treatment response can be evaluated using growth prediction models. In an effort to improve the accuracy of these prediction models, Ranke et al. (J Clin Endocrinol Metab 95(3):1229–37) proposed a novel ‘data-driven’ approach based on a quantitative analysis of a large cohort of patients from the Pfiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…If a child's growth is as predicted and the responsiveness is as expected, GH therapy should be continued at the same dose. Kaspers et al [7] reported that by using population modelling, a small proportion of patients may respond better than predicted and, therefore, their GH dose could be reduced, resulting in a more cost-effective therapy. On the other hand, a proportion of patients may not respond as well as expected.…”
Section: Actual Vs Predicted Growth Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…If a child's growth is as predicted and the responsiveness is as expected, GH therapy should be continued at the same dose. Kaspers et al [7] reported that by using population modelling, a small proportion of patients may respond better than predicted and, therefore, their GH dose could be reduced, resulting in a more cost-effective therapy. On the other hand, a proportion of patients may not respond as well as expected.…”
Section: Actual Vs Predicted Growth Responsesmentioning
confidence: 99%
“…However, each child responds to a dose of rhGH in a unique way due to their genetic, metabolic and physical characteristics. Whilst many children with a given diagnosis respond as expected to rhGH treatment and are likely to reach the goals of intended treatment [5], some children respond less well [6] and some may respond better than expected [7].…”
Section: Introductionmentioning
confidence: 99%
“…1 It is one of the most common genetic disorders, affecting approximately one in every 2,000 live-born females. 2 , 3 Girls with TS typically experience gonadal dysfunction and short stature.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the major therapeutic advance that use of rhGH represents, there remains considerable variability of long-term growth response, with many patients not achieving their genetic potential, even in classical GH deficiency [37]. To address this variability, a range of models can predict the growth response to GH therapy given for different indications [38][39][40][41][42]. Working from such models, height velocity using a standard dose of rhGH 0.3 mg/kg/week will increase by 2 cm/year in children with GH deficiency, compared with SGA and Turner syndrome patients.…”
Section: Growth Prediction Modelsmentioning
confidence: 99%